Personalized nanomedicine for CNS diseases. Issue 5 (May 2018) - Kaushik, Ajeet; Jayant, Rahul Dev; Bhardwaj, Vinay; Nair, Madhavan
Highlights: CNS diseases are increasing globally with added socioeconomic burden. Unavailability of effective therapy make situation more challenging. Novel therapeutic agents and methods to deliver them to the brain are urgently required. Personalized nanomedicine approach based on nano-biotechnology seems problem solving. Novel treatments, analytical tools and computational are in demand to manage CNS diseases. Abstract : Central nervous system (CNS) diseases are rapidly increasing globally. Currently used therapeutic agents to treat CNS diseases exhibit significant efficacy. However, the inability of these drugs to cross the blood–brain barrier (BBB) and invasiveness of the technologies to achieve localized drug delivery in disease-specific parts of the brain have thwarted pain-free and complete treatment of CNS diseases. Therefore, the safe, non-invasive, and targeted delivery of drugs to the brain using nanoparticles (NPs) is currently receiving considerable research attention. Here, we highlight advances in state-of-the-art personalized nanomedicine for the treatment of CNS diseases (with a focus on dementia), the related challenges, possible solutions, and prospects for nano-enabled personalized medicine.